New Approaches to Evaluating the Performance of Corporate–Community Partnerships: A Case Study from the Minerals Sector - Esteves, Ana Maria (Journal of business ethics, 2011)
A continuing challenge for researchers and practitioners alike is the lack of data on the effectiveness of corporate–community investment programmes. The focus of this article is on the minerals industry, where companies currently face the challenge of matching corporate drivers for strategic partnership with community needs for programmes that contribute to local and regional sustainability. While many global mining companies advocate a strategic approach to partnerships, there is no evidence currently available that suggests companies are monitoring these partnerships to see if they do, in fact, represent ‘strategic’ investments. This article argues that applying the management concept of ‘investment performance’ to corporate–community partnerships requires questioning traditional evaluation methods that focus on the results of programmes or activities. We adopt a case study approach to introduce an evaluation framework that considers performance from both corporate and community perspectives and that conceptualises partnership performance as comprising four aspects: (1) the contribution of the partnership to the overall portfolio of a company’s community investment programmes, (2) the appropriateness of the partnership model, (3) the effectiveness of the partnering relationship and (4) the ability of the partners to achieve programme goals. The application of this evaluation framework to an established corporate–community partnership programme provided some useful insights as to how partnership performance can be improved.